2005
DOI: 10.1007/s11240-004-4957-x
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Robinia pseudoacacia

Abstract: Cryopreservation of Robinia pseudoacacia explants by vitrification achieved 78% survival following the stepwise preculture of shoot tips in (0.3 + 0.5 + 0.7 M) sucrose with a 80 min incubation in PVS2; compared to 87% survival after desiccation of explants to 30% water content, following 3 days alginate bead (with glycerol and sucrose treatments) preculture in 0.7 M sucrose.Abbreviations: DMSO -dimethylsulfoxide; LN -liquid nitrogen; MS -Murashige and Skoog medium (Murashige and Skoog, 1962)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Shoot tips of American chestnut were precultured stepwise for 96 h in sucrose-enriched solution with concentrations ranging from 0.25 to 1.0 M, which significantly shortened the preculture duration. The progressive increase of sucrose concentration during preculture treatments was found to improve the survival and regeneration of numerous species such as Corrigin grevillea [ 98 ], sugar beet [ 99 ], black locust [ 100 ], potato [ 101 ], and grapevine [ 102 ]. Jorquera et al [ 44 ] indicated that shoot tips of European chestnut provided a sufficient recovery rate when precultured in sucrose concentrations between 0.1 to 0.4 M for two days at 4 °C, while shoot tips precultured in higher sucrose concentration (0.7 M) showed a significantly decreased recovery (7.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Shoot tips of American chestnut were precultured stepwise for 96 h in sucrose-enriched solution with concentrations ranging from 0.25 to 1.0 M, which significantly shortened the preculture duration. The progressive increase of sucrose concentration during preculture treatments was found to improve the survival and regeneration of numerous species such as Corrigin grevillea [ 98 ], sugar beet [ 99 ], black locust [ 100 ], potato [ 101 ], and grapevine [ 102 ]. Jorquera et al [ 44 ] indicated that shoot tips of European chestnut provided a sufficient recovery rate when precultured in sucrose concentrations between 0.1 to 0.4 M for two days at 4 °C, while shoot tips precultured in higher sucrose concentration (0.7 M) showed a significantly decreased recovery (7.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Somatic seedlings were regenerated from L. tulipifera cultures stored in liquid nitrogen for 48 h (Vendrame et al 2001). Verleysen et al (2005) reported the successful cryopreservation of R. pseudoacacia via vitrification and encapsulation-dehydration. Seeds of T. cordata show 65-75% seedling emergence after freezing in liquid nitrogen, if seeds are dried to 11-20% moisture content and scarified before freezing (Chmielarz 2002).…”
Section: In Vitro Culturementioning
confidence: 99%